Exploring the addictive processes in repetitive self-harm through a grounded theory approach: “It always felt like a choice until it didn’t” - Millie Witcher; Sarah Rowe; Sally Marlow; Jennifer Heath (PLoS ONE, 2025)
Introduction There is limited empirical research to suggest repetitive self-harm can be understood or conceptualised as an addictive behaviour. However, few empirical studies have investigated this and yielded conflicting results. This study aims to explore to what extent can repetitive self-harm be conceptualized as an addictive behaviour. Methods The study employed the principles of Constructivist Grounded Theory to guide the collection and analysis of data from 15 adults with current or past experience of repetitive self-harm. Results Thirteen categories were identified within the data that depicted participants journeys with self-harm over time. ‘Starting’ to self-harm (category 1) and participants’ description of ‘needing to punish myself’ (category 2) led to self-harm ‘feeling addictive’ (category 3). Once self-harm had become repetitive, ‘having the urge to self-harm’ (category 4) and experiencing a ‘conflicting relationship with self-harm and self’ was ongoing for participants (category 5). Throughout each incidence of self-harm, participants described a “cycle of self-harm”, in which self-harm had different functions and consequences: ‘managing emotions’ (category 6), ‘allowing me to function’ (category 7), ‘caring for myself’ (category 8), ‘controlling’ (category 9) and ‘feeling guilt and shame after self-harm’ (category 10). All participants described ‘responding to other’s reactions’ to their self-harm (category 11), six discussed ‘breaking the self-harm cycle’ (category 12) and six participants described ‘relapsing’ (category 13) and returning to self-harm following a period of abstinence. Conclusion This study has provided a conceptual model of processes that maintain engagement in repetitive self-harm, discussed in relation to addiction literature. Clinical practice could consider working alongside the client to identify where they feel they are within the self-harm cycle in relation to changing their self-harm behaviours.